Addressing Workforce Disparities by Improving the Academic Resilience and Professionalism of Health Science Students Through Structured and Targeted Supports - Selameab, Tehout; Mason, Meghan R. (Frontiers in Public Health, 2021)
Background: Saint Catherine University’s undergraduate program in Public Health is the institution’s second most popular major, drawing students from diverse racial, economic, cultural and educational backgrounds. This has presented significant opportunities and challenges with regard to providing students and faculty with the needed academic and professional development to ensure graduates embody the skills needed for today’s Public Health workforce. The objective of this study was to identify potential structured institutional supports to graduate Public Health professionals from diverse communities to advance health equity. A secondary objective was to determine whether the needed supports for Public Health students might differ from peers in other health programs, specifically Nursing. Methods: Using a mixed methods approach and a convenience sample, data was gathered from Public Health students, nursing students, faculty and staff from November 2019 through July 2020. The survey assessed stress, grit, and demographic factors. Focus group topics included: academic resilience and professionalism, supports and gaps in the current institutional structure with respect to mitigating student stressors and opportunities for programmatic solutions. Results: In total, 53 Public Health and 32 in Nursing student completed the survey. Nursing students tended to be farther along in their undergraduate careers, less likely to have failed a class, and more likely to have recently been laid off from a job. Public Health students reported more support from parents, but less support from friends and classmates than their Nursing peers. Most Nursing and Public Health students reported unmanaged stress, and similar average GRIT scores (3.51 v. 3.41, p=0.43), respectively. In focus groups, students described a series of stressors including working full-time while attending school, family expectations, difficulty with time management, and learning how to acclimate to college norms. University staff and faculty identified financial pressures as a primary student stressor in addition to complex lives including managing family crises. Conclusions: Study findings are being used to identify or adapt professional development supports in undergraduate Public Health programs. Through supporting a diverse undergraduate student population in Public Health, a future workforce from communities most impacted by health disparities will emerge.